3
$\begingroup$

I have a question about an argument from a proof in Hideyuki Matsumura's "Commutative Ring Theory" on page 9, Theorem 2.5:

Let $(A,\mathfrak{m})$ be a local ring; then a finitely generated projective module $M$ over $A$ is free.

The proof works as follows:

Choose a minimal $A$-basis $\omega_1,...,\omega_n$ of $M$. Take into account that "minimal" means that there cannot exist another system of generators $b_1,..., b_m \in M$ with $m < n$ and $M = \sum_{i=1} ^m A b_i$.

Define a surjective map $\varphi:F \to M$ from the free module $F = Ae_1 \oplus \cdots \oplus Ae_n$ to $M$ by $\varphi(\sum a_i e_i) = \sum a_i\omega_i$. If we set $K = \operatorname{Ker}(\varphi)$ then, from the minimal basis property

$$\sum a_i \omega_i =0 \Rightarrow a_i \in \mathfrak{m} \text{ for all } i. $$

Thus $K \subset \mathfrak{m}F$. Because $M$ is projective, there exists $\psi: M \to F$ such that $F = \psi(M)\oplus K$, and it follows that $K = \mathfrak{m}K$. (???)

On the other hand, $K$ is a quotient of $F$, therefore finite over $A$, so that $K = 0$ by Nakayama and $F = M$.

Question: why the fact that $F = \psi(M)\oplus K$ implies that $K = \mathfrak{m}K$?

$K \subset \mathfrak{m}F$, then we can deduce $K=K∩mF$$K∩(m \psi(M)\oplus mK)$ But why the last is equal to $mK$?

Thank you for your kind help.

$\endgroup$
3
$\begingroup$

You have $K=K\cap \mathfrak mF=K\cap(\mathfrak m\psi(M)\oplus \mathfrak mK)$. Since $K\cap \psi(M)=0$ ($\because F=\psi(M)\oplus K$), you get $K\cap\mathfrak m\psi(M)=0$. Thus $K=\mathfrak mK$ as required.

$\endgroup$
0
$\begingroup$

Let $k=A/\mathfrak{m}$ be the residue field of $A$. Tensor the exact sequence $G \rightarrow F\rightarrow M\rightarrow 0$ with $k$ (where $G$ is a free module minimally projecting on $K$) to get $F/\mathfrak{m}F\simeq M/\mathfrak{m}M$ ($K\subseteq \mathfrak{m}F$). Now tensor the equality $F=\psi(M)\oplus K$ with $k$ and count vector space dimension.

$\endgroup$
4
  • $\begingroup$ We cannot deduce the consequence without using tensor product? Tensor product appears much later in this text. $\endgroup$ – Nekojiru Dec 15 '20 at 7:20
  • $\begingroup$ Sure we can, tensor products are unnecessary, $\mathfrak{m}F=\mathfrak{m}\psi(M)\oplus\mathfrak{m}K$, so just use the definition of a direct sum. $\endgroup$ – Phoenix Dec 15 '20 at 7:43
  • $\begingroup$ How do we use the definition of a direct sum? We know K⊂mψ(M)×mK.From here, why we can say K⊂mK? $\endgroup$ – Nekojiru Dec 15 '20 at 7:51
  • $\begingroup$ Every element $f\in F$ has a unique representation $f=a+b$, $a\in \psi(M)$, $b\in K$. If $k\in K$ is arbitrary, then $k$ as an element of $F$ (it is a submodule) can be written in the above form as $0+k$. On the other hand every element of $\mathfrak{m}F$ has a unique decomposition $x+y$, $x\in \mathfrak{m}\psi(M)\subseteq \psi(M)$, $y\in \mathfrak{m}K\subseteq K$. So $k$ as an element of $\mathfrak{m}F$ and hence $F$ can be written uniquely as $x+y$, $x\in \mathfrak{m}\psi(M)$, $y\in \mathfrak{m}K$. Therefore $x=0$, $y=k$, so $K=\mathfrak{m}K$. $\endgroup$ – Phoenix Dec 15 '20 at 17:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.